2006
DOI: 10.1086/504869
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Study of 2000 Narrow Line Seyfert 1 Galaxies from the Sloan Digital Sky Survey. I. The Sample

Abstract: This is the first paper in a series dedicated to the study of the emission-line and continuum properties of narrow line Seyfert 1 galaxies (NLS1s). We carried out a systematic search for NLS1s from objects assigned as "QSOs" or "galaxies" in the spectroscopic sample of the Sloan Digital Sky Survey Data Release 3 (SDSS DR3) by a careful modeling of their emission lines and continua. The result is a uniform sample comprising ∼ 2 000 NLS1. This sample dramatically increases the number of known NLS1 by a factor of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
316
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(339 citation statements)
references
References 86 publications
(86 reference statements)
18
316
1
Order By: Relevance
“…Figure 1 illustrates the observational situation by plotting the distribution of a representative SDSS quasar subsample (Schneider et al 2010) in the z − B absolute magnitude plane. Note that only sources listed as quasars in the Schneider et al (2010) catalogs are shown, so that a large population of local active galactic nuclei (AGN; Koehler et al 1997) and AGN with the narrowest broad lines (FWHM < 1000 km s −1 ; Zhou et al 2006) are not shown in the lower part of the plot. The low-z yellow box identifies a range of absolute magnitudes where quasars are rare in the local Universe (they would be easily detected, but they do not exist in large numbers) and belong to the high-luminosity tail of the optical luminosity function (Cheng et al 1985;Grazian et al 2000;Richards et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates the observational situation by plotting the distribution of a representative SDSS quasar subsample (Schneider et al 2010) in the z − B absolute magnitude plane. Note that only sources listed as quasars in the Schneider et al (2010) catalogs are shown, so that a large population of local active galactic nuclei (AGN; Koehler et al 1997) and AGN with the narrowest broad lines (FWHM < 1000 km s −1 ; Zhou et al 2006) are not shown in the lower part of the plot. The low-z yellow box identifies a range of absolute magnitudes where quasars are rare in the local Universe (they would be easily detected, but they do not exist in large numbers) and belong to the high-luminosity tail of the optical luminosity function (Cheng et al 1985;Grazian et al 2000;Richards et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Trends and correlations have been identified using, first, small samples and, later, corroborated by larger surveys (e.g. [32,33]). Many scenarios have been considered to explain these properties.…”
Section: Introductionmentioning
confidence: 74%
“…[2,11] and reference therein) and low black hole masses (typically of order 10 6 M , e.g. [1,33,28]). While these scenarios can elucidate the nuclear properties of NLS1s, they hardly explain the origin of the fundamental differences between NLS1s and BLS1s and, in particular, that NLS1s appear to be more than just Seyfert 1s with narrow lines.…”
Section: Introductionmentioning
confidence: 99%
“…A sample of very narrow NLSy1s (blue triangles; Zhou et al [24]) is also shown. The dot-dashed lines indicate the limits for NLSy1s (magenta) and for Pop.…”
Section: Figurementioning
confidence: 98%